2021
DOI: 10.52687/2348-8956/822
|View full text |Cite
|
Sign up to set email alerts
|

Drug Eluting Bioresorbable Cellulose Acetate/PEO/HPMC Composite With Propolis Extracts for Suturing Application

Abstract: A detailed study on a drug eluting cellulose based resorbable suture material, elaborately characterized for its mechanical and physico-chemical properties is presented. The biocompatibility of the material was tested with 3T3 [NIH] cells. The material's ability to be heat sterilized has been verified with thermogravimetric analysis which exhibited stability up to 200°C. Drug eluting property of the material loaded with propolis and without propolis has been assessed and the corresponding kinetics was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The importance of propolis in wound healing may be attributed to its bacterial and biofilm formation inhibition, which was demonstrated against staphylococci, streptococci, and some antibiotic-resistant tuberculosis strains [ 21 ]. Previous studies have demonstrated the beneficial role of propolis in nanostructured lipid carriers for stopping breast cancer evolution [ 22 ], in cellulose acetate/polyethylene oxide/hydroxypropyl methyl cellulose composite to obtain a drug-releasing resorbable suture material [ 23 ], and in dressing for wound healing based on bacterial cellulose (BC) incorporating propolis and Cinnamomum cassia essential oil, which, as expected, inhibited the growth of Gram-positive bacteria, while also affecting the growth of Gram-negative bacteria [ 16 ]. Propolis was also used to induce antimicrobial activity in nanocellulose-containing polymer composites [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of propolis in wound healing may be attributed to its bacterial and biofilm formation inhibition, which was demonstrated against staphylococci, streptococci, and some antibiotic-resistant tuberculosis strains [ 21 ]. Previous studies have demonstrated the beneficial role of propolis in nanostructured lipid carriers for stopping breast cancer evolution [ 22 ], in cellulose acetate/polyethylene oxide/hydroxypropyl methyl cellulose composite to obtain a drug-releasing resorbable suture material [ 23 ], and in dressing for wound healing based on bacterial cellulose (BC) incorporating propolis and Cinnamomum cassia essential oil, which, as expected, inhibited the growth of Gram-positive bacteria, while also affecting the growth of Gram-negative bacteria [ 16 ]. Propolis was also used to induce antimicrobial activity in nanocellulose-containing polymer composites [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%